Swimming economy (energy cost) and efficiency - Di Prampero, P. E.; Pendergast, D.; Zamparo, P. (World book of swimming: From science to performance, 2012)
The energy cost per unit distance (i. e the economy of swimming, C) is given by the ratio E / v where E is the net (above resting) metabolic power and v is thc swimming speed. The contribution of the aerobic and anaerobic energy sources to E in swimming competitions differs according to the distance covered; it is independent of swimming style, gender or skill and depends essentially upon the duration of the exercise in swimming, C increases with the speed with a non linear function; for a given speed, C is the lowest for the front crawl, followed by the backstroke, the butterfly and the breaststroke. C is essentially determined by the hydrodynamic resistance (Wd): the higher Wd the higher C; and by the propelling efficiency (np): the higher np thelower C. Hence, all factors influencing Wd and/or np will result in proportional changes in C. The concepts of economy and efficicncy are strictly related; hence, this chapter is also devoted to an analysis of the efficiencies in swimming, a summary of the values reported in the literature is also presented from a "historical point of view". Last but not least, the factors setting performance ( Emax and C) are briefly reviewed in view of a proper planning of swim training.